Effect of pralidoxime on coronary perfusion pressure during cardiopulmonary resuscitation in a pig model - Yong Hun Jung; Dong Hyun Ryu; Kyung Woon Jeung; Joo-Young Na; Dong Hun Lee; Byung Kook Lee; Tag Heo; Yong Il Min (Clinical and Experimental Emergency Medicine, 2019)
Objective Pralidoxime is widely used for the treatment of organophosphate poisoning. Multiple studies have reported its vasoconstrictive property, which may facilitate the restoration of spontaneous circulation (ROSC) after cardiac arrest by increasing the coronary perfusion pressure (CPP). 2,3-Butanedione monoxime, which belongs to the same oxime family, has been shown to facilitate ROSC by reducing left ventricular ischemic contracture. Because pralidoxime and 2,3-butanedione monoxime have several common mechanisms of action, both drugs may have similar effects on ischemic contracture. Thus, we investigated the effects of pralidoxime administration during cardiopulmonary resuscitation in a pig model with a focus on ischemic contracture and CPP. Methods After 14 minutes of untreated ventricular fibrillation, followed by 8 minutes of basic life support, 16 pigs randomly received either 80 mg/kg of pralidoxime (pralidoxime group) or an equivalent volume of saline (control group) during advanced cardiovascular life support (ACLS). Results Mixed-model analyses of left ventricular wall thickness and chamber area during ACLS revealed no significant group effects or group-time interactions, whereas a mixed-model analysis of the CPP during ACLS revealed a significant group effect (P=0.038) and group-time interaction (P<0.001). Post-hoc analyses revealed significant increases in CPP in the pralidoxime group, starting at 5 minutes after pralidoxime administration. No animal, except one in the pralidoxime group, achieved ROSC; thus, the rate of ROSC did not differ between the two groups. Conclusion In a pig model of cardiac arrest, pralidoxime administered during cardiopulmonary resuscitation did not reduce ischemic contracture; however, it significantly improved CPP.